PERAN PEREMPUAN BOTI DALAM PELESTARIAN TENUN IKAT: KAJIAN ETNOGRAFI DI DESA BOTI, NUSA TENGGARA TIMUR - Lanny Isabela Dwisyahri Koroh; Yebester Benu; Prima Wati Ximenes; Cindi Padu Lemba; Supriati Timbu Dona; Anggiska Niku (Jurnal Lazuardi, 2026)
This study examines the role of Boti women in preserving the ikat weaving tradition in Boti Village, South Central Timor Regency, East Nusa Tenggara. Ikat weaving is a cultural heritage that holds not only aesthetic value but also serves as a marker of female identity within the social structure of the Boti community. Using an ethnographic approach with in-depth interview and participant observation techniques, this research identifies three dimensions of women's roles in preserving ikat weaving: (1) the ritual role through the Noina ceremony as an intergenerational transmission of weaving knowledge; (2) the economic role of ikat weaving as a pillar of household welfare; and (3) the social identity role in which weaving proficiency becomes a prerequisite for female adulthood and marriageability in Boti. The findings indicate that Boti women are not merely tradition practitioners but primary agents who actively reproduce, transmit, and sustain weaving knowledge along with its cultural value system. The Noina ritual, lasting up to seven days, serves as a specialized mechanism that symbolically and functionally unites Boti women with weaving tools. The existence of 15 ikat weaving groups in Boti Village supported by village funds reflects the synergy between cultural preservation and women's economic empowerment.